Examining the Role of Magnetic Resonance Imaging (MRI) in Cerebral Ischemic Stroke: A Cross-Sectional Study - Nadia Moheem, Ameet Kumar Lalwani, Shaiq Hussain, Asma Ajlas, Khair Muhammad, Noreen Ismail (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to examine the role of Magnetic Resonance Imaging (MRI) when detecting cerebral ischemic stroke. Study design: A cross-sectional study Place and Duration: This study was conducted at Sandeman Provincial Hospital/ Bolan medical complex hospital Quetta, Quetta from March 2021 to March 2022 Methodology: Age and gender distribution of infarcts was done to find out the territory and location of the blood vessels involved. Overall, 52 individuals were involved in this research. Every patient was clinically suspected to have a cerebral ischemic stroke during the time span of our research. HDXT software with 1.5 Tesla 16 channel GE was used to perform the MRI scans. FLAIR axial, T1WI axial, T2WI axial and coronal, ADC maps, and gradient echo axial were the sequences used. SWI was optional. Results: The age group which was above 60 years included more percentage of males than females. It was seen that in the age group above 60 years, infarction was the most common and hypertension was the most common risk factor. Hemiplegia (Weakness) was seen to be the most common clinical presentation. It was seen that middle cerebral artery (MCA) territory infarcts had a slight rise on the right side. On the diffusion-weighted imaging (DWI), restricted diffusion was seen from subacute as well as acute infarcts along with a low apparent diffusion coefficient (ADC)valves. T2 FLAIR was normal in acute infarcts, but changes were reflected by DWI. Practical implication : Expanding the rationale for acute stroke thrombolysis may be more rationally accomplished by comprehending the clinical implications of numerous valuable MRI findings and thoroughly incorporating those factors into treatment decision-making. Conclusion: No radiation hazard is seen in MRI and it is non-invasive. The multiplanar imaging ability and grey-white resolution of the MRI perceive the subtle lesions. Infarcts are detected early due to the sensitivity of MRI to altered water content. Keywords: magnetic resonance imaging, stroke, cerebral infarcts,